2023
DOI: 10.3390/healthcare11121715
|View full text |Cite
|
Sign up to set email alerts
|

Frailty in Kingdom of Saudi Arabia—Prevalence and Management, Where Are We?

Abstract: A recent report from the United Nations state that the percentage of elderly individuals in the Kingdom of Saudi Arabia (KSA) will witness a sharp increase in the next three decades (5.6% in 2017 to 23% by 2050). This situation will lead to an increased prevalence of comorbidities and hence, will require close monitoring and constant care of such individuals who are prone to suffer from complications such as arthritis, cardiovascular disorders, diabetes, neurological disorders, etc. Frailty is one such age-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…However, the development process of ML tools must be improved[ 27 ] for the diagnosis, prognosis, and treatment of various diseases to improve health sectors broadly. [ 28 29 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, the development process of ML tools must be improved[ 27 ] for the diagnosis, prognosis, and treatment of various diseases to improve health sectors broadly. [ 28 29 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…Frailty increases the li adverse consequences, including an increased risk of falls, the need for hosp and mortality [35,36]. Previously conducted research results indicated that t of pre-frailty and frailty in the Kingdom of Saudi Arabia was 47.3% and 21. tively [37]. Evidence indicates that an increased level of physical performance an increase in the intensity of physical activity, which could reduce the level of Walking is considered the most preferred form of PA, particularly for older walking on a regular basis may confer significant health benefits in terms of physical performance and fitness as well as preventing the incidence of physic in older individuals [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Frailty increases the likelihood of adverse consequences, including an increased risk of falls, the need for hospitalization, and mortality [35,36]. Previously conducted research results indicated that the situation of prefrailty and frailty in the Kingdom of Saudi Arabia was 47.3% and 21.4%, respectively [37]. Evidence indicates that an increased level of physical performance is related to an increase in the intensity of physical activity, which could reduce the level of frailty [38].…”
Section: Discussionmentioning
confidence: 99%
“…The study provides references for health policy decision-making regarding the prevention of frailty progression in Asian countries. Alshanberi [ 17 ] also pays attention to the prevalence of frailty. In his paper, he presents studies on frailty focused on older people living in the Kingdom of Saudi Arabia.…”
mentioning
confidence: 99%